2020
DOI: 10.1074/jbc.ra120.014236
|View full text |Cite
|
Sign up to set email alerts
|

Structural and catalytic roles of the human 18S rRNA methyltransferases DIMT1 in ribosome assembly and translation

Abstract: Ribosomal RNA (rRNA)-modifying enzymes participate in ribosome assembly. However, whether the catalytic activities of these enzymes are important for the ribosome assembly and other cellular processes is not fully understood. Here, we report the crystal structure of wildtype human dimethyladenosine transferase 1 (DIMT1), an 18S rRNA N6,6-dimethyladenosine (m26,6A) methyltransferase, and results obtained with a catalytically inactive DIMT1 variant. We found that DIMT1+/- heterozygous HEK 293T cells have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 59 publications
(87 reference statements)
3
44
2
Order By: Relevance
“…In fact, analyses performed in the model bacterium E. coli [this study and ( 25 )] provide a very similar picture in this organism, where no major effect on protein synthesis and stability, and only discrete effects on a subset of the E. coli proteome could be scored [this study and ( 25 )]. This is in stark contrast to a recent analysis using human cell culture where a greater effect on proteostasis was observed ( 122 ). However, the use of overexpression of catalytic inactive KsgA/Dim1, in a haploinsufficient human KsgA/Dim1 background, may account for the exacerbating effect on cellular transcription/translation observed under these experimental conditions ( 122 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In fact, analyses performed in the model bacterium E. coli [this study and ( 25 )] provide a very similar picture in this organism, where no major effect on protein synthesis and stability, and only discrete effects on a subset of the E. coli proteome could be scored [this study and ( 25 )]. This is in stark contrast to a recent analysis using human cell culture where a greater effect on proteostasis was observed ( 122 ). However, the use of overexpression of catalytic inactive KsgA/Dim1, in a haploinsufficient human KsgA/Dim1 background, may account for the exacerbating effect on cellular transcription/translation observed under these experimental conditions ( 122 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in stark contrast to a recent analysis using human cell culture where a greater effect on proteostasis was observed ( 122 ). However, the use of overexpression of catalytic inactive KsgA/Dim1, in a haploinsufficient human KsgA/Dim1 background, may account for the exacerbating effect on cellular transcription/translation observed under these experimental conditions ( 122 ). Indeed, overexpression of catalytic inactive KsgA/Dim1 leads to dominant-negative effects on various aspects of prokaryotic cellular physiology [( 16 ), this study see Figure 2 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, we introduced a highly conservative E85Q mutation to eliminate the methyltransferase activity of Dim1p ( Figure 1E ), but unfortunately, this E85Q mutant is still defective in SSU biogenesis ( Figures S5A and S5B ) and rRNA processing ( Figure S6B ). Recent structural work reveals that the E85A mutation has little impact on the overall conformation of human DIMT1 ( Shen et al, 2020 ), and conceivably, the E85Q mutation would be expected to be even less disruptive. Still, even such a conservative change leads to rRNA processing defects.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in methylation patterns can be associated with methylase/demethylase activity; it was previously shown that the total demethylase (VaDem1 and VaDem2) expression in grape cell lines was lower than in the leaves of the native plant [ 72 ]. Although the biological functions of the rRNA modifications remain mainly unclear, alterations in the rRNA modifications occur during development, environmental changes, and disease, and dysregulation of methylation can affect ribosomal ligand binding and translation accuracy [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%